Labour related provisions in international investment agreements - Boie, Bertram (Geneva, 2012)
"Today’s international investment law is characterized by significant fragmentation. Different disciplines of investment regulation have grown over time in form of separate treaty regimes and address different aspects of international investment matters. This paper provides an overview over the main treaties and regulatory aspects from the perspective of relevance for labour issues. To this end, the paper gives an overview over main labour related provisions in WTO Law (the GATS and the TRIMs agreement), and in bilateral and preferential trade and investment agreements. The picture gained by the overview reveals considerable diversity. Partly, diversity is driven by the distinct regulatory intent of different agreements. In particular, it appears to make a difference whether agreements target investment protection, investment liberalization or both. Overall, the analysis of labour issues across the range of different regimes suggests that there is scope for innovation to deal with labour in a more coherent and more effective manner in the context of international economic regulation."